Gulf-selective postsynthetic functionalization of a soluble hexabenzoovalene - Baumgärtner, Kevin; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2018)
The interest in 2D-annulated polycyclic aromatic hydrocarbons (PAHs) has risen in recent years due to promising applications in using PAHs for organic electronics. The larger the PAHs, the more insoluble they are, making their characterization and especially selective functionalization difficult. Triptycene end-capping has been introduced to circumvent the problem of low solubility of a hexabenzoovalene (HBO). Additionally, the tendency to form single-crystals for X-ray diffraction is preserved. The good solubility of the HBO makes it possible to selectively difunctionalize the compound in the “gulf” region to change electronic properties of the π-system, which has been investigated photophysically as well as electrochemically.
Gesehen am 06.03.2020